2007
DOI: 10.1021/ja0734086
|View full text |Cite
|
Sign up to set email alerts
|

Distortion/Interaction Energy Control of 1,3-Dipolar Cycloaddition Reactivity

Abstract: Huisgen's 1,3-dipolar cycloaddition reactions, extraordinarily versatile methods for heterocycle synthesis, are now used in materials chemistry, drug discovery, and chemical biology. 1,2 The 1,3-dipoles range from the familiar atmospheric components, ozone and nitrous oxide, to the synthetically valuable azides of click chemistry fame. 1 Frontier molecular orbital (FMO) theory has provided a powerful model for the qualitative understanding of reactivity and regioselectivity, based upon electronic properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
496
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 883 publications
(513 citation statements)
references
References 13 publications
14
496
1
2
Order By: Relevance
“…when more distorted the TS is with respect to the separated reagents, higher the activation energy. This finding, which is a computational assertion of Hammond's postulate [9], does not resolve the question why the activation energies of these 32CA reactions depend on the geometry deformations [7,8].…”
Section: Understanding the Reactivity Of Ai 1b Possessing A Carbon Psmentioning
confidence: 83%
See 3 more Smart Citations
“…when more distorted the TS is with respect to the separated reagents, higher the activation energy. This finding, which is a computational assertion of Hammond's postulate [9], does not resolve the question why the activation energies of these 32CA reactions depend on the geometry deformations [7,8].…”
Section: Understanding the Reactivity Of Ai 1b Possessing A Carbon Psmentioning
confidence: 83%
“…On the order hand, unlike the non-polar Diels-Alder reaction between butadiene 9 and ethylene 3, which has a high activation energy of ca. 25 kcal·mol -1 [35], the non-polar 32CA reactions between TACs and ethylene 3 have activation energies that range from 1 to 15 kcal·mol -1 [7,8]. Note that ethylene 3 is a poor electrophile and a poor nucleophile that cannot participate in polar reactions.…”
Section: Understanding the Reactivity Of Ai 1b Possessing A Carbon Psmentioning
confidence: 99%
See 2 more Smart Citations
“…[9,23] Recently, Houk and co-workers reported that the energy to distort 1,3-dipoles and dipolarophiles to their transition state geometries is related to the activation energies of these kinds of 1,3-dipolar cycloaddi- tion. [24] In addition, Houk has also shown by DFT calculations that the mechanism of 1,3-dipolar cycloadditions of phenyl azide and cyclooctyne derivates are concerted and nearly synchronous. This observation is supported by the performed calculations.…”
Section: Resultsmentioning
confidence: 99%